IMPROVING THE TAXATION PROCEDURE OF FOREIGN TRADE ACTIVITY: PROBLEMS, CUSTOMS CONTROL AND DIGITAL ADMINISTRATION (European Journal of Economics, Finance and Business Development, 2026)
The article examines scientific and practical directions for improving the taxation procedure of foreign trade activity on the basis of the third chapter materials of the research work. The study focuses on the main problems and disproportions in the taxation of export-import operations, the growth of problematic foreign trade receivables, the need to improve customs payments and customs control, and the transformation of tax-customs administration through digital technologies. The paper argues that foreign trade taxation should not be interpreted only as a fiscal source of budget revenue. It should be considered as an integrated regulatory mechanism that combines fiscal stability, export incentives, customs transparency, risk-based control and institutional predictability. Particular attention is paid to the repatriation of assets, recognition of hopeless debts, VAT accounting for export operations, electronic contract monitoring and the transition from punitive control to preventive analytical supervision.